Plasmodium knowlesi: Clinical Presentation and Laboratory Diagnosis of the First Human Case in a Scottish Traveler. Issue 5 (26th May 2014) - Cordina, Claire J.; Culleton, Richard; Jones, Brian L.; Smith, Catherine C.; MacConnachie, Alisdair A.; Coyne, Michael J.; Alexander, Claire L.
Abstract : The first imported case of Plasmodium knowlesi in Scotland is described in a 33‐year‐old female with a travel history to Borneo. The patient ceased to take antimalarial prophylaxis after 4 days of her 10‐day visit and presented with a history of fever, rigor, vomiting, and diarrhea after 13 days on her return to the UK. Malaria antigen detection using the Optimal‐IT and Binax‐NOW kits was negative. Unusual trophozoite‐like structures were observed under microscopic examination and the identification of P. knowlesi performed by a nested polymerase chain reaction (PCR) gel‐based approach was confirmed by using a PCR‐sequencing assay.